Employees are losing: Have workplace laws gone too far?. (June 2019) - Bornstein, Josh
Concern about the economic, social and political cost of growing income inequality is propelling a debate about the loss of employee bargaining power – both in Australia and other Organisation for Economic Co-operation and Development countries. The evidence of a pronounced decline in the bargaining power of employees in the Australian labour market is overwhelming. The decline is consistent with a collapse in workplace bargaining as a result of a bargaining framework that has not kept up with major structural change in the labour market. In the absence of decisive legislative intervention, the decline of employee bargaining power is likely to continue.